Síntese e caracterização de carreadores de oxigênio para combustão com recirculação química obtidos via reação de combustão assistida por microondas - Melo, Vitor Rodrigo de Melo e (2012)
Perovskites oxides win importance by its properties and commercials applications, they have a high thermal stability, have conductive properties, electrical, catalytic, electro catalytic, optical and magnetic, and are thermally stable. Because of these properties, are being widely studied as carriers of oxygen in the process of power generation with CO2 capture. In this work, the base carrier system La1-xMexNiO3 (Me = Ca and Sr) were synthesized by the method via the combustion reaction assisted by microwave. were synthesized from the combustion reaction method by microwave process. This method control the synthesi`s conditions to obtain materials with specific characteristics. The carriers calcined at 800 ° C/2h were analyzed by thermal analysis (TG-DTA), to verify its thermal stability, X-ray diffraction (XRD) to verify the phase formation, with subsequent refinement by the Rietveld method, to quantify the percentage of phases formed, the surface area by BET method was determined, scanning electron microscopy (SEM) was obtained to evaluate the material morphology and temperature programmed reduction (TPR) was done to observe the metallic phase of the nickel. After all proposed characterization and analysis of their results can be inferred to these oxides, key features so that they can be applied as carriers for combustion reactions in chemical cycles. The final products showed perovskite-type structures K2NiF4 (main) and ABO3.